An analysis of benefits and risk information on pharmaceutical web sites for the treatment of menopause. (17th April 2013) - Charbonneau, Deborah H.
Abstract: Background: As the Internet is a source of information for many health consumers, there is a need to evaluate the information about prescription drugs provided on pharmaceutical manufacturers' web sites. Objectives: Using a sample of pharmaceutical manufacturers' web sites for the treatment of menopause, the main objective of this study was to evaluate consumer‐oriented information about benefits and risks of prescription drugs for the treatment of menopause provided on pharmaceutical web sites. Methods: Pharmaceutical manufacturers' web sites for analysis were identified using a list of U.S. FDA‐approved hormone therapies for the treatment of menopause. Results: This study revealed substantial gaps in how benefits and risk information were presented on the web sites. Specifically, information about the benefits was prominent while risk information was incomplete and challenging to find. Further, references to the scientific literature to support claims advertised about prescription drug benefits were not provided. Conclusions: Given the lack of scientific evidence to support claims of benefits and limited disclosure about risks, more information is needed for consumers to be able to weigh the benefits and risks of these treatments for menopause. Overall, these findings provide guidance for evaluating drug information provided on pharmaceutical web sites.